(untitled) (Islamic Sciences Journal, 2025)
Praise be to Allah, by whose grace good deeds are completed. May peace and blessings be upon the Seal of the Prophets, through whom Allah concluded the divine messages, and upon his family, companions, and all who follow them in righteousness until the Day of Judgment. This research examines the non-canonical readings of Al-Yazidi as mentioned in Al-Durr Al-Masun fi ‘Ulum Al-Kitab Al-Maknun (The Preserved Pearl in the Sciences of the Hidden Book) by Abu Al-‘Abbas, Shihab Al-Din Ahmad bin Yusuf bin ‘Abd Al-Da’im, known as Al-Samin Al-Halabi (d. 756 AH), focusing on the first third of the Quran. The study defines Al-Farsh (variant readings) and anomalous readings, provides a brief biography of Al-Yazidi, and presents Al-Samin Al-Halabi’s discussions on Al-Yazidi’s readings. It also addresses potential linguistic or interpretive challenges in these readings and compares them with other canonical readings.